PICROILMENITE FROM KIMBERLITES OF THE DALDYN FIELD, YAKUTIA - Alymova N.V.; Kostrovitskii S.I.; Ivanov A.S.; Serov V.P. (My University, 2004)
The compositional structure of kimberlite fields is among the blank spots in the geology of kimberlite volcanism. Identification of pipe clusters within a kimberlite field is based on the geographic principle only, i.e., the spaial association of kimberlite bodies. We used one of the typomorphic kimberlite minerals-picroilmenite in-order to analyze the kibmberlite field structure. The abundance of picroilmenite, its stability during the hypergene disintegration of kimberlites and the formation of diamond collectors, and other specific features define a major role or this mineral in prospecting work.